Peanut allergy is common among hazelnut‐sensitized subjects but is not primarily the result of IgE cross‐reactivity. Issue 3 (31st December 2014) - Masthoff, L. J.; van Hoffen, E.; Mattsson, L.; Lidholm, J.; Andersson, K.; Zuidmeer‐Jongejan, L.; Versteeg, S. A.; Bruijnzeel‐Koomen, C. A.; Knulst, A. C.; Pasmans, S. G.; van Ree, R.
Abstract Background Hazelnut and peanut are botanically unrelated foods, but patients are often sensitized and allergic to both, for reasons that are not well understood. Methods To investigate molecular cosensitization and cross‐reactivity to peanut in hazelnut‐sensitized individuals, children (n = 81) and adults (n = 80) were retrospectively selected based on sensitization to hazelnut. IgE to hazelnut extract, Cor a 1, 8, 9 and 14, to peanut extract, Ara h 1, 2, 3, 8 and 9, and to Bet v 1 was determined by ImmunoCAP. Allergy to hazelnut and peanut was established by DBPCFC and/or detailed clinical history. Patients were either tolerant or displayed subjective or objective symptoms to either food. IgE cross‐reactivity between hazelnut and peanut storage proteins was assessed by reciprocal ImmunoCAP inhibition experiments. Results Of the 161 hazelnut‐sensitized subjects, 109 (68%) were also sensitized to peanut, and 73 (45%) had clinical expression of allergy to peanut that was not associated with the presence or severity of hazelnut allergy. Instead, it was associated with IgE reactivity to peanut storage proteins, in particular Ara h 2. No cross‐reactivity could be detected between Ara h 2 and Cor a 14, and 2 of 13 subjects displayed extensive cross‐reactivity between 11S globulins; in plasma of both individuals, Ara h 3 almost completely inhibited IgE binding to Cor a 9. Conclusions Peanut allergy is not primarily the result of IgE cross‐reactivity to hazelnut storage proteins. IgE to Cor a 14 and Ara h 2 may serve as useful markers of primary sensitization to hazelnut and peanut, respectively.